2016
DOI: 10.18632/oncotarget.10169
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells (CSCs), cervical CSCs and targeted therapies

Abstract: Accumulating evidence has shown that cancer stem cells (CSCs) have a tumour-initiating capacity and play crucial roles in tumour metastasis, relapse and chemo/radio-resistance. As tumour propagation initiators, CSCs are considered to be promising targets for obtaining a better therapeutic outcome. Cervical carcinoma is the most common gynaecological malignancy and has a high cancer mortality rate among females. As a result, the investigation of cervical cancer stem cells (CCSCs) is of great value. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
112
1
15

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 199 publications
(196 reference statements)
1
112
1
15
Order By: Relevance
“…Moreover, our data show that this increased expression markedly promoted migration of cervical cancer cells, suggesting that GLDC is involved in metastasis promotion. Since GLDC functioned in driving tumorigenesis in cancer stem cells (CSCs) [9], and CSCs is critical for tumor metastasis [34][35][36], GLDC might be the connection between CSCs and metastasis. In one hand, metastasis could be triggered by CSCs via elevated activities of glycine metabolism enzymes including GLDC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our data show that this increased expression markedly promoted migration of cervical cancer cells, suggesting that GLDC is involved in metastasis promotion. Since GLDC functioned in driving tumorigenesis in cancer stem cells (CSCs) [9], and CSCs is critical for tumor metastasis [34][35][36], GLDC might be the connection between CSCs and metastasis. In one hand, metastasis could be triggered by CSCs via elevated activities of glycine metabolism enzymes including GLDC.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells (CSCs) are a small subpopulation of immortal cancer cells, capable of long-term self-renewal, and differentiation into heterogeneous cancer cell lineages (Bandhavkar, 2016). Although the existing of CSCs is still controversial, recently a number of studies have identified CSCs in several types of solid tumor, such as renal cancer, breast cancer, lung cancer, liver cancer, prostate cancer, melanoma, and in leukemia (Huang and Rofstad, 2016). CSCs are known as the source of primary and metastatic cancer, and the root of chemo- and radio-therapy resistance (Sales et al, 2007; Colak and Medema, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to targeting cell surface markers, exosomes can also target CSC specific signal pathways. For example, Wnt, Notch, Hippo, Hedgehog, NF-κB, and TGF-β pathways are crucial to maintain the CSC capacities such as self-renewal, differentiation, tumor initiation, and drug resistance (Dandawate et al, 2016; Huang and Rofstad, 2016; Rinkenbaugh and Baldwin, 2016). Using exosomes loaded with inhibitors, miRNAs, or siRNAs to target these pathways can be considered an alternative way to achieve CSC targeting.…”
Section: Introductionmentioning
confidence: 99%
“…The HPV oncoprotein E6 has been demonstrated to participate in maintenance of stem‐cell phenotype and stemness in cervical cancer cells . Multiple stem‐cell specific markers and functional assays have been used to identify putative CSCs for both in vitro and in vivo studies . Notably it is believe that the aberrant expression of certain stem‐cell‐related nuclear transcription factors, such as octamer‐binding transcription factor 4 (OCT4), SOX2, and NANOG, could contribute to cervical carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%